AB0999 Development of An Activity Disease Score in Patients with Uveitis (UVEDAI). (15th July 2016) - Pato, E.; Martin-Martinez, A.; Castellό, A.; Méndez-Fernandez, R.; Muñoz-Fernández, S.; Cordero-Coma, M.; Martinez-Costa, L.; Valls, E.; Reyes, M.; Francisco, F.; Esteban, M.; Fonollosa, A.; et al.
Abstract : Background: Uveitis is defined as inflammation of the uvea. As standardized and validated outcome measures are lacking in uveitis management. Objectives: To develop a disease activity score for patients with uveitis and determine its discriminating ability to classify patients based on the level of activity. Methods: Multicenter cross-sectional observational study. The construct "uveitis inflammation activity" was defined as intraocular inflammation. Seven dimensions and 14 items were identified and were agreed upon by experts via a two-round Delphi technique. Patients diagnosed with uveitis, who were aged five years or older and who presented inflammatory activity at the time of their visit, were selected. An ordinal logistic regression model was built in which the dependent variable was uveitis inflammatory activity (mild, moderate, or severe). Modeling accuracy for patient classification was assessed by the Area Under the Curve (AUC). Two AUC measures were calculated: one for discriminating mild versus moderate and severe activity level of uveitis, and another for mild and moderate versus severe activity. Results: 195 patients were included. The regression model revealed an associations between intraocular activity level and an elevated number of anterior chamber cells (OR4 cells vs 0 cells = 27.85; 95% CI: 3.42; 226.75), a high degree of vitreous haze (ORsevere vs null = 3.95; 95% CI: 1.40; 11.16), macular edema over 315mm (OR>315 vs ≤315 = 3.58; 95% CI: 1.56; 8.21), inflammatory vessel sheathing (OR=4.43; 95% CI: 1.71; 11.53), higher patient evaluation scores (OR1-unit increase = 1.23; 95% CI: 1.09; 1.39), the presence of papilitis (OR=4.05; 95% CI: 1.18; 13.92) and increased numbers of choroidal or retinal lesions (OR≥6 vs 0 =4.99; 95% CI =1.08; 23.01). The discriminatory capacity of UVEDAI was 87% for differentiating patients with mild uveitis from those with moderate or severe uveitis, and 88% for discriminating patients with mild or moderate uveitis versus those with severe uveitis. Conclusions: UVEDAI assesses and classifies patients depending on global ocular inflammatory activity with high discriminative capacity. Disclosure of Interest: None declared